2023
DOI: 10.3390/nano13131931
|View full text |Cite
|
Sign up to set email alerts
|

Synergies between Fibrillated Nanocellulose and Hot-Pressing of Papers Obtained from High-Yield Pulp

Abstract: To extend the application of cost-effective high-yield pulps in packaging, strength and barrier properties are improved by advanced-strength additives or by hot-pressing. The aim of this study is to assess the synergic effects between the two approaches by using nanocellulose as a bulk additive, and by hot-pressing technology. Due to the synergic effect, dry strength increases by 118% while individual improvements are 31% by nanocellulose and 92% by hot-pressing. This effect is higher for mechanical fibrillate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Therefore, it was decided to manufacture dogbone specimens without CNF and perform the corresponding mechanical analysis. In addition, Negro et al [ 23 ] demonstrated that the dry strength of thermopressed paper sheets was more affected by hot-pressing settings than by the addition of micro/nanofibrillated cellulose, indicating that CNF may not be necessary to improve the mechanical performance of thermopressed products.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it was decided to manufacture dogbone specimens without CNF and perform the corresponding mechanical analysis. In addition, Negro et al [ 23 ] demonstrated that the dry strength of thermopressed paper sheets was more affected by hot-pressing settings than by the addition of micro/nanofibrillated cellulose, indicating that CNF may not be necessary to improve the mechanical performance of thermopressed products.…”
Section: Resultsmentioning
confidence: 99%